Collegiate Business Mathematics - Berston, Hyman Maxwell; Fisher, Paul (Homewood, Illinois: Irwin Inc., 1982)
The material presented in this text is specifically for students and it will enable them to solve problems in everyday basic mathematics satisfactorily and also those most frequently found in business. In each unit of the material, there are examples provided which explain the use of this material.
Includes Index.
ne 13/03/2018, ijb 20/03/2019
Loans
Keywords: Business Mathematics